(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this work, experimental studies of the effect of fiber curvature on the strength and ultimate deformations of epoxy carbon plastic samples under loading are carried out. On the basis of the experimental studies carried out, the static characteristics of the composite layered material, which are promising for use in the structures under consideration, have been determined. Based on the test results, it was demonstrated that in the design calculations for the products under consideration, it is possible to use static characteristics, since an increase in the deformation rate of the material leads to an increase in strength and, therefore, the calculation results will provide an additional margin of safety.